Expulsionscapes. Logics of Expulsion and Economies of Eviction in Milan (Italy) - Giacomo Pozzi (Archivio Antropologico Mediterraneo)
Drawing on ethnographic research carried out between October 2015 and December 2016, in this article I employ an anthropological gaze to show the socially and analytically central role evictions play in the contemporary world as a mechanism for producing social exclusion, inequality and difference. In the first section, I outline some contextual elements to frame the housing issue in Italy, while in the second I bring certain conceptual and methodological tools from both anthropology and other disciplines to bear on interpreting the phenomenon of residential eviction. In the third section, I present several case studies investigated during my fieldwork to illustrate four «logics of expulsion» that pave the way for understanding the richness of each «local place» as part of a globally encompassing phenomenon which, borrowing from Appadurai, I have defined as expulsionscape.